Decision making : 5 steps to better results - Luecke, Richard, (Harvard business essentials series., 2006)
"Decision making is a critical part of management, and bad choices can damage careers and the bottom line. This book offers the tools and advice managers need to avoid common biases and arrive at and implement decisions that are both sound and ethical.The Harvard Business Essentials series provides comprehensive advice, personal coaching, background information, and guidance on the most relevant topics in business. Whether you are a new manager seeking to expand your skills or a seasoned professional looking to broaden your knowledge base, these solution-oriented books put reliable answers at your fingertips."--EBSCO.